New records and new species of the munidopsine squat lobsters (Decapoda: Anomura: Galatheidae: Munidopsinae) from Australia - Taylor, Joanne; Ahyong, Shane T.; Andreakis, Nikos (Zootaxa, 2010)
Nine species of Munidopsis Whiteaves, 1784, and one species of Galacantha A. Milne-Edwards, 1880 (Crustacea: Decapoda: Galatheidae) are reported from the continental shelf of Australia. Two species are new to science, M. comarge sp. nov. and M. vesper sp. nov. Munidopsis vesper is presently known only from Western Australia, but M. comarge ranges from Western Australia to New Zealand. Six species are reported for the first time from Australian waters, G. subspinosa Macpherson, 2007, M. andamanica MacGilchrist, 1905, M. crenatirostris Baba, 1988, M. hirsutissima Balss, 1913, M. levis (Alcock & Anderson, 1894) and M. nitida (A. Milne-Edwards, 1880). A range extension within Australia is reported for M. dasypus Alcock, 1894 and M. kensleyi Ahyong & Poore, 2004. These new records expand the number of Munidopsis species previously recorded from Australian waters from 15 to 22 and the number of Galacantha species from three to four. A key and illustrated guide to the species now known from Australia is provided.